Atividade do jogo e desenvolvimento infantil: implicações sociais para a construção da consciência da criança na escola - Nunes, Rodrigo Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Este trabalho constituiu-se como pesquisa-intervenção, cujo objetivo era investigar estudantes em atividade de jogo na escola e compreender o processo de desenvolvimento de sua consciência, considerando suas ações, manifestações e expressões durante sua atividade e a presença do fenômeno social da alienação nesse processo. A pesquisa aconteceu numa escola pública municipal de Ensino Fundamental I da cidade de Presidente Prudente/SP e os sujeitos foram alunos de 06-07 anos de idade, pertencentes a uma sala de aula do 2º. ano da referida instituição. Inicialmente foram registrados os comportamentos e falas dos sujeitos em atividades gerais na escola, tanto em sala de aula, como nos intervalos e momentos de entrada e saída da escola. Posteriormente foram observadas as atividades de jogo desenvolvidas pelos membros do GEIPEE-thc (Grupo de Estudos, Intervenção e Pesquisa em Educação Escolar e Teoria histórico-cultural), grupo do qual o pesquisador faz parte, que realiza projeto de intervenção na escola objeto da pesquisa...

This work was constituted as an intervention research, which aimed to investigate students in play activity at school and understand the process of development of your consciousness, considering their actions, manifestations and expressions during their activity and the presence of the social alienation phenomenon in this process. The research took place on a municipal public school of basic education (first cycle) on the city of Presidente Prudente / SP and the subjects were students from 06-07 years age, belonging to a 2nd. year classroom of that institution. Initially was record the subjects’ behavior and speech in general activities at school, both in classroom, in the intervals and moments which they in and out the school. Later were observed the play activities undertaken by members of GEIPEE-thc (Study, Intervention and Research Group of School Education and cultural-historical theory), group which the researcher is part, and which performs the intervention project in school, research’s object. Besides the observations, conversations were held with the teachers of school, during pedagogical meetings and specific meetings with managers. We understand that play, understood as historical human-generic building, occurs from the reconstruction by children of the social relations being in society… (Complete abstract click electronic access below)
Keywords: Educação; Jogos; Consciência; Alienação (Psicologia social); Escolas; Education